Remote sensing applications in monitoring and management of soil and water pollution - Kanahiya, Krishan; Sundha, Parul; Bundela, D. S. (Indian Farming, 2025)
Pollution of soil and water is major problem all around the world that effects the condition of ecosystem, agricultural productivity and well-being of human lifestyles. Traditionally, tracking and managing these problems require a lotof fieldwork, which can be laborious, time consuming and has limited both spatial and geographical coverage. A useful alternative is remote sensing, offers a promising alternative by making it possible to gather data from multiple sensors on a large scale and frequently. This article addresses the newest developments, methods and data types in the field of remote sensing, which investigates how remote sensing can be used to track and control soil and water pollution.